The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00007890-200208150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Transplant tumor registry: donor related malignancies

Abstract: The United States incidence of donor related tumors is extremely small. The donor related tumor death rate is also extremely small, particularly when compared with waiting-list mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(142 citation statements)
references
References 17 publications
6
134
1
1
Order By: Relevance
“…The first reported case of cancer transmission from a living organ donor was a breast cancer transmitted from a donor wife to recipient husband, but lung, lymphoma, and renal cell cancer have also been recorded (Kauffman et al 2002). The young age of most living organ donors provides a degree of protection against cancer transmission because of the strong ageassociated risk of cancer; however, many of the common cancers such as breast, colon, prostate, cervix, and in Australia also melanoma, are sufficiently prevalent that one case might be expected to be transmitted unknowingly every 5000 living donations.…”
Section: Living Donor Assessment For Cancer Riskmentioning
confidence: 99%
“…The first reported case of cancer transmission from a living organ donor was a breast cancer transmitted from a donor wife to recipient husband, but lung, lymphoma, and renal cell cancer have also been recorded (Kauffman et al 2002). The young age of most living organ donors provides a degree of protection against cancer transmission because of the strong ageassociated risk of cancer; however, many of the common cancers such as breast, colon, prostate, cervix, and in Australia also melanoma, are sufficiently prevalent that one case might be expected to be transmitted unknowingly every 5000 living donations.…”
Section: Living Donor Assessment For Cancer Riskmentioning
confidence: 99%
“…Thus far, there have been 17 documented cases of donor-transmitted malignancies to liver transplant recipients (Table 2). 48,49 Based on these data, cancer histologies with prohibitively high transmission risk include melanoma and choriocarcinoma. The cancer-free interval must also be considered on evaluation of donors with a history of malignancy.…”
Section: Donors With Malignanciesmentioning
confidence: 99%
“…However, tumors that may possess the potential of unpredictable recurrence include breast, colon, lung, melanoma, and renal cell carcinoma. 49 Donors with histories of primary central nervous system (CNS) tumors have also been evaluated. 48 Between January 1992 and December 1999, 397 of 42,340 cadaver donors had a history of CNS tumors.…”
Section: Donors With Malignanciesmentioning
confidence: 99%
“…Although there have been instances in which cessation of immunosuppression has contributed to the cure of a donor-derived neoplasm, including broncho- genic carcinoma transferred by kidney transplantation, 3 progression of malignancy despite restitution of the immune system also has been well documented. 4,5 Therefore, in today's climate of critical organ shortage, for a potential donor with known malignancy, either past or current, the estimated risk for cancer transmission tempers the evaluation, consideration, and acceptance of his or her organs by the individual transplant physicians and candidates. Although rare, as documented by several recent reviews, transmission of donor cancer still occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been suggested that emergent retransplantation may be the best treatment option, and several case reports have attested to the validity of this recommendation. 5,6,[10][11][12] Ours is the first case in the literature of donor cancer transmission despite explantation and retransplantation immediately on identification of the donor malignancy, before the identification of tumor transmission in the recipient. Clearly, tumor cells had escaped the confines of the transplanted liver within 1 week after transplantation and gained access to the general circulation.…”
Section: Discussionmentioning
confidence: 99%